A ultra-stable point of care nanozyme-based kit for cTnI detection in human serum - Sun, Mingfei; Yang, Zhan; Ma, Ziwei; Wu, Jinbo; Lu, Shaoying (Frontiers in Bioengineering and Biotechnology, 2025)
Home discovery of myocardial infarction can significantly improve the rate of treatment. Cardiac troponin I (cTnI), as a biochemical marker that has been introduced into clinical diagnosis and treatment guidelines, can effectively predict the occurrence of myocardial infarction. We constructed highly stable nanozyme based on Fe3O4 nanoparticles and prepared rapid detection reagents for myocardial infarction by modifying anti-cTnI antibodies. The results showed that the nanozyme with an average particle size of 200 nm had peroxidase activity and could effectively catalyze 3,3′, 5,5′-tetramethylbenzidine (TMB). With a sensitivity of up to 1.5 ng/mL, the kit showed superior performance than commercial colloidal gold assay kits, and could effectively detect cTnI in serum with an overall compliance rate of 92.1%. The study provides a new approach to home detection of heart attacks.